Health Monitoring of An Existing RC Structure Considering Seismic Analysis Using Analysis Tools Staad - Sourabh Sahu; Ravindra Kumar Raj (International Journal of Scientific Research in Civil Engineering, 2021)
Seismic retrofitting is for the most part done to meet the seismic wellbeing prerequisites. The arranging of changes to existing structures contrasts from new arranging through a significant condition; the current development must be taken as the premise of all arranging and building activities. India is one of the most seismic tremor inclined nations on the planet and has encountered a few significant or moderate quakes during the most recent 15 years.  Around 50-60 % of the absolute region of the nation is helpless against seismic movement of changing powers. Many existing structures don't meet the seismic quality prerequisite. In this study we are performing health monitoring on existing old structure G+2, using rebound hammer to evaluate its present strength and analyze the structure using analysis tool staad.pro.  In this study we are performing time history analysis (el-centrino) with retrofitting over weak members.
Keywords: Staad.pro; Time History; Non Destructive Test; Rebound Hammer; Existing Structure; Retrofitting; Analysis